Systems Chemistry: Martha Grover. Issue 3 (21st February 2019) - Grover, Martha A.
Abstract: Martha Grover is a Professor in the School of Chemical and Biomolecular Engineering at the Georgia Institute of Technology (USA) and is a member of the NSF/NASA Center for Chemical Evolution. She is a current member of the ChemSystemsChem Editorial Board.